Flow Injection Amperometric Evaluation of Trolox Equivalent Antioxidant Capacity of Chocolates with Different Cocoa Content at a Boron-Doped Diamond Electrode - Arbneshi, Tahir; Frangu, Arbër; Frühbauerová, Michaela; Červenka, Libor; Berisha, Liridon; Kalcher, Kurt; Sýs, Milan (Food technology and biotechnology, 2021)
RESEARCH BACKGROUND: The objective of this paper is to introduce an instrumentally simple analytical tool for determination of cocoa solid content in chocolates. This electroanalytical method is based on amperometric oxidation of all present antioxidants in chocolates at boron-doped diamond electrode (BDDE) that is integrated in a flow injection analysis (FIA) wall-jet electrode system. EXPERIMENTAL APPROACH: As part of optimisation, thirteen commonly occurring antioxidants were investigated using cyclic voltammetry at the BDDE in 0.1 mol/L phosphate buffer with different methanol (MeOH) content. Working parameters, such as MeOH volume fraction, flow rate and detection potential, were optimised. Principally, the height of the oxidation peak (current response) representing the oxidation of the sum of antioxidants (total antioxidant content; TAC) was expressed as Trolox equivalents. RESULTS AND CONCLUSIONS: For analytical purpose, a linear range from 5 to 100 mg/L described by regression equation and characterised by high correlation coefficient R2=0.9994 was achieved. Obtained high positive correlation between the determined values of Trolox equivalent antioxidant capacity (TEAC) and cocoa mass fractions characterised by correlation coefficient of 0.9187 for eight randomly selected samples (one white, two milk, and five dark chocolates) confirmed that cocoa solids represent the main source of antioxidants (reducing agents). NOVELTY AND SCIENTIFIC CONTRIBUTION: The research demonstrates that TEAC values could be considered as an additional marker of cocoa content in the chocolate analysis to the commonly used theobromine (authenticity of food products). The developed FIA could therefore serve as simple analytical tool in the food quality control.
Keywords: boron-doped diamond electrode; amperometry; cocoa mass fraction in chocolate; Trolox equivalent antioxidant capacity; flow injection analysis